Structure-activity relationships of oomycete elicitins uncover the role of reactive oxygen and nitrogen species in triggering plant defense responses - Janků, Martina; Jedelská, Tereza; Činčalová, Lucie; Sedlář, Antonín; Mikulík, Jaromír; Luhová, Lenka; Lochman, Jan; Petřivalský, Marek (Plant science, 2022)
Elicitins are proteinaceous elicitors that induce the hypersensitive response and plant resistance against diverse phytopathogens. Elicitin recognition by membrane receptors or high-affinity sites activates a variety of fast responses including the production of reactive oxygen species (ROS) and nitric oxide (NO), leading to induction of plant defense genes. Beta-cryptogein (CRY) is a basic β-elicitin secreted by the oomycete Phytophthora cryptogea that shows high necrotic activity in some plant species, whereas infestin 1 (INF1) secreted by the oomycete P. infestans belongs to acidic α-elicitins with a significantly weaker capacity to induce necrosis. We compared several mutated forms of β-CRY and INF1 with a modulated capacity to trigger ROS and NO production, bind plant sterols and induce cell death responses in cell cultures of Nicotiana tabacum L. cv. Xanthi. We evidenced a key role of the lysine residue in position 13 in basic elicitins for their biological activity and enhancement of necrotic effects of acidic INF1 by the replacement of the valine residue in position 84 by larger phenylalanine. Studied elicitins activated in differing intensity signaling pathways of ROS, NO and phytohormones jasmonic acid, ethylene and salicylic acid, known to be involved in triggering of hypersensitive response and establishment of systemic resistance.
Keywords: Cryptogein; rostliny; sekvence aminokyselin; Nitric oxide; Reactive oxygen species; Infestin; Plant defense responses; reaktivní formy kyslíku; dusík; fungální proteiny; Plants; bílkoviny řas; Reactive Oxygen Species; kyslík; Algal Proteins; Fungal Proteins; vztahy mezi strukturou a aktivitou; Elicitins; Amino Acid Sequence; Oxygen; Structure-Activity Relationship; Nitrogen; Phytophthora